2003
DOI: 10.1111/j.1440-1746.2004.03262.x
|View full text |Cite
|
Sign up to set email alerts
|

Absence of hemochromatosis associated Cys282Tyr HFE gene mutation and low frequency of hemochromatosis phenotype in nonalcoholic chronic liver disease patients in India

Abstract: Almost 10% of nonalcoholic CLD patients in India have iron overload, but this is independent of C282Y mutation of the HFE gene. Large population based studies are recommended to investigate the prevalence of this rare disorder in India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 21 publications
(45 reference statements)
2
17
1
1
Order By: Relevance
“…Neither the patients with heterozygous H63D mutation, nor the lone compound heterozygote individual (C282Y/H63D) had primary iron overload. These observations are in concordance with previous studies from India where C282Y has not been identified except for a single individual from Punjab in northern India, and a more widespread distribution of H63D mutation has been reported [4][5][6][7][8]. The H63D mutation is widely distributed in nearly all populations with a variable allele frequency and haplotype analysis suggests that it has occurred earlier to the C282Y mutation.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Neither the patients with heterozygous H63D mutation, nor the lone compound heterozygote individual (C282Y/H63D) had primary iron overload. These observations are in concordance with previous studies from India where C282Y has not been identified except for a single individual from Punjab in northern India, and a more widespread distribution of H63D mutation has been reported [4][5][6][7][8]. The H63D mutation is widely distributed in nearly all populations with a variable allele frequency and haplotype analysis suggests that it has occurred earlier to the C282Y mutation.…”
supporting
confidence: 91%
“…The H63D mutation is widely distributed in nearly all populations with a variable allele frequency and haplotype analysis suggests that it has occurred earlier to the C282Y mutation. Its frequency varies from 9.1% to 13.9% in different studies from India [5][6][7][8] and several studies have showed that even H63D homozygotes have no evidence of iron overload. An independent role of H63D mutation in causing hereditary hemochromatosis is not established yet.…”
mentioning
confidence: 99%
“…In these particular regions, the association of HFE mutations with iron overload is minimal and varied. [7][8][9][10][11][12][13][14][15] There have only been a few brief reports of non-HFE hemochromatosis in Asia, which appear to be isolated mutations with most cases around Eastern Asia. [16][17][18] In the Indian subcontinent, reports are even fewer with only 2 cases of type 4 hemochromatosis identified and no cases of JH.…”
Section: Introductionmentioning
confidence: 99%
“…These findings indicate that the frequency of cryptogenic chronic hepatitis in the general population is as high as 5.4%. Other studies in patients with mild chronic liver test abnormalities have indicated a frequency of cryptogenic chronic hepatitis or cryptogenic cirrhosis ranging from 2 to 38% depending on the intensity of the screening protocol (the inclusion of tests for celiac disease and hereditary hemochromatosis) and the criteria for NAFLD (metabolic syndrome or liver tissue examination) [10,74,[78][79][80][81].…”
Section: Frequency Of Cryptogenic Chronic Hepatitismentioning
confidence: 98%
“…Experiences in Scandinavia and North America have reported similar associations between cryptogenic cirrhosis [87,89] HLA DRB1*03 or DRB1*04 [206][207][208] Interface hepatitis and/or plasma cells [182] pANCA, SLA, ASGPR [3,7,84,102] IAIHG score C 10 pretreatment [89] Corticosteroid response [2,[61][62][63] Nonalcoholic fatty liver disease 21-63% [50,59,79] Overweight or obesity [10,11] Type 2 diabetes [50] Hyperlipidemia [79] Macrosteatosis [111] Ballooned hepatocytes [12] Mallory-Denk bodies [12] Megamitochondria [12] Hepatitis B virus or hepatitis C virus 2-58% [31,49,121] Epidemiological risk factors HBV DNA or HCV RNA [31,49] Hereditary hemochromatosis 4-23% [81,156,157] Transferrin saturation [ 45% [135] Family history [135] Homozygosity C282Y [26] Increased hepatic iron concentration [135] Alpha-1 antitrypsin deficiency 2-27% [23,[158][159][160] MS, MZ, SZ or ZZ phenotype [158,…”
Section: Cryptogenic Chronic Hepatitis and Nafldmentioning
confidence: 99%